1999
DOI: 10.1086/307147
|View full text |Cite
|
Sign up to set email alerts
|

Mass and Metallicity of Five X‐Ray–bright Galaxy Groups

Abstract: We present ASCA X-ray observations of a sample of five groups selected from a crosscorrelation of the ROSAT All-Sky Survey with the White et al. optical catalog of groups. These X-ray bright groups significantly increase the number of known systems with temperatures between 2 and 3 keV. They have element abundances of roughly 0.3⊙ that are typical of clusters, but their favored ratio of Si/Fe abundance is lower than the cluster value. Combining the ASCA results with ROSAT imaging data, we calculate total masse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
1

Year Published

2000
2000
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 59 publications
6
40
1
Order By: Relevance
“…However, this also did not modify the low-energy spectrum. Other authors have also noted the loss in lowenergy response from the SIS appearing as an increase in the inferred column density (Hwang et al 1999 ;Mukai & Smale 2000). We found that an additional SIS-1 absorption of 4.0 ] 1021 cm~2 for GX 354[0 and 2.4 ] 1021 cm~2 for KS 1731[260 was required in our observation.…”
Section: Observation and Resultssupporting
confidence: 75%
“…However, this also did not modify the low-energy spectrum. Other authors have also noted the loss in lowenergy response from the SIS appearing as an increase in the inferred column density (Hwang et al 1999 ;Mukai & Smale 2000). We found that an additional SIS-1 absorption of 4.0 ] 1021 cm~2 for GX 354[0 and 2.4 ] 1021 cm~2 for KS 1731[260 was required in our observation.…”
Section: Observation and Resultssupporting
confidence: 75%
“…The luminosity function derived by Burns et al (1996) is a smooth extrapolation of the rich cluster X-ray luminosity function and is consistent with the luminosity function Henry et al (1995) derived from their X-ray selected sample of groups. Follow-up work on some of the brighter sources in the WBL catalog indicates that many of these objects are more massive than typical groups with gas temperatures of 2-3 keV (Hwang et al 1999). These systems are important because they represent the transition objects between poor groups and rich clusters.…”
Section: Rosat Surveys Of Groupsmentioning
confidence: 99%
“…Since the determinations of and r c depend somewhat on the extension of the X-ray surface brightness profile if the available data extend only out to 2 or 3 times the core radius, we truncate each S X ðrÞ at the maximum radii set by the X-ray surface brightness limits S limit ¼ 2 Â 10 À14 and 2 Â 10 À15 ergs s À1 arcmin À2 cm À2 in the 0.5-2.0 keV band, respectively. These two values have approximately covered White et al (1997) and 21 data points of groups ( filled stars) by Mulchaey et al (1996) and Hwang et al (1999) within different radii, which are properly binned according to temperature and radius. Fig.…”
Section: Radial Distribution Of Gas Fractionmentioning
confidence: 99%
“…Next, we choose the two group samples of Mulchaey et at. (1996) and Hwang et al (1999) used in the construction of the f star -T relation (see eq.…”
Section: Radial Distribution Of Gas Fractionmentioning
confidence: 99%